Development biology reference book-based utilization telang flower (Clitoria ternatea L.) for food packaging natural indicators - Noviyanti, Rahmawati Eka; Kusumaningrum, Serafica Btari Christiyani; Darmawan, Ericka (JPBIO (Jurnal Pendidikan Biologi), 2024)
This study was based on the lack of knowledge and sources of information and the absence of media development regarding the potential utilization of telang flowers (Clitoria ternatea L.) as a natural indicator of food packaging among the general public. Therefore, the development of information media in the form of a biology reference book based on the utilization of the potential of telang flowers as a natural indicator of food packaging, assessing the feasibility of the developed reference book, and the community's response to the developed biology reference book. The research method used is R&D (Research and Development) with the 4-D development model modified into 3-D, which consists of 3 stages Define, Design, and Develop. The biology reference book developed is classified as feasible to use because it obtained an average score of 92.66% (very good) on the material expert validation and a percentage of 79.60% (enough) on the media expert validation. The results of the community's response are good categories with an average percentage of 80.99%. So, it is feasible to use a source of information for the general public. This research produced a source of information in the form of a biology reference book for the general public